Assessment of complete lymph node dissection in patients with melanoma: A systemic review and meta-analysis - Jiangying Xuan; Ming Zhu; Lu Wang; Zixu Gao; Kangjie Shen; Ming Ren; Yanlin Li; Chuanyuan Wei; Jianying Gu (Chinese Journal of Plastic and Reconstructive Surgery, 2023)
Background: Complete lymph node dissection (CLND) for patients with melanoma remains controversial. This meta-analysis aimed to compare the prognoses and complications between the CLND and control groups (patients who receive adjuvant treatment or observation only) in patients with sentinel lymph node (SLN)-positive melanoma. Methods: The PubMed, Embase, Cochrane, and Web of Science databases were searched for cohort studies and randomized clinical trials (RCTs) conducted between 1964 and 2022, and the quality of the studies was assessed using the Cochrane risk-of-bias tool and Newcastle-Ottawa Scale. Hazard ratios (HR) or risk ratios (RR) with 95% confidence intervals (CIs) were calculated for each outcome. Heterogeneity and sensitivity tests were also conducted, and publication bias tests were performed when the pooled number of studies was >10. Results: Fifteen studies, including 11 cohort studies and 4 RCTs, were enrolled and assessed for quality. Analysis of overall survival showed no significant difference between the CLND and control groups (HR=1.02, 95% CI: 0.69–1.51, P=0.922). Similarly, recurrence-free survival (HR=0.84, 95% CI: 0.6–1.16, P=0.287), disease-free survival (HR=1.06, 95% CI: 0.65–1.72, P=0.82), and disease-specific survival (HR=0.84, 95% CI: 0.59–1.21, P=0.355) showed no difference between the two groups. CLND did not reduce the risk of recurrence (RR=0.98, 95% CI: 0.8–1.2, P=0.851). Conclusion: Remarkably, patients who underwent CLND were more likely to have complications such as flap necrosis and lymphedema than the controls. CLND does not improve patient prognosis and may increase the incidence of complications.